Perancangan Aplikasi Pelaporan Kerusakan Infrastruktur Publik Berbasis Android di Pulau Lepar Kabupaten Bangka Selatan untuk Mendukung Konsep Smart Island - Adinda Nayla; Reza Al Fajar (Teknik: Jurnal Ilmu Teknik dan Informatika, 2026)
This study aims to design and develop an Android-based public infrastructure damage reporting application on Lepat Island, South Bangka Regency, as an effort to support the Smart Island concept. The background of this study is the continued use of a manual reporting system that causes delays in handling and a lack of transparency. The method used is Agile which includes the stages of system design, implementation, testing and periodic evaluation. Data collection techniques are carried out through observation, interviews, and literature studies. The results of the study are an Android-based application that allows the public to report infrastructure damage with features to upload photos, descriptions, and GPS-based locations. In addition, the application provides report history and status monitoring features to increase transparency. The implementation results show that the use of mobile technology can improve service efficiency, speed up the reporting process, and increase community participation. This application is expected to support the implementation of Smart Governance and Smart Island in the region.